2016
DOI: 10.1159/000445634
|View full text |Cite
|
Sign up to set email alerts
|

Geniposide Prevents Hypoxia/Reoxygenation-Induced Apoptosis in H9c2 Cells: Improvement of Mitochondrial Dysfunction and Activation of GLP-1R and the PI3K/AKT Signaling Pathway

Abstract: Background/Aims: Myocardial ischemia/reperfusion injury is a major cause of morbidity and mortality associated with coronary heart disease. Many studies have demonstrated that natural products are promising chemotherapeutic drugs counteracting the loss of cardiomyocytes. Thus, the purpose of the present study was to investigate the effects of geniposide, a traditional Chinese herb extract from Gardenia jasminoides J. Ellis, on cardiomyocyte apoptosis induced by hypoxia/reoxygenation (H/R) in H9c2 cells, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 45 publications
2
77
0
Order By: Relevance
“…Previous studies demonstrated that GLP-1R played an anti-apoptosis role in INS-1 cells [23], H9c2 cells [24] and astrocytes [15]. GLP-1 binding to GLP-1R resulted in body weight loss due to decreased food intake.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that GLP-1R played an anti-apoptosis role in INS-1 cells [23], H9c2 cells [24] and astrocytes [15]. GLP-1 binding to GLP-1R resulted in body weight loss due to decreased food intake.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is too soon for some of these procedures to be used in clinical practice [32-35]. Other procedures showed disappointing results when were translated to the clinic [36-38].…”
Section: Discussionmentioning
confidence: 99%
“…Wells were randomly divided into groups. After incubation at different experimental conditions, neurons in 24-well clusters were processed for detecting of cell viability by LDH release kit (Nanjing Jiancheng Biotechnology, Haimen, China) as described previously [18]. Briefly, cell supernatants were collected, mixed with reagents of the LDH assay kit, and incubated at room temperature for 5 min, absorbance value of LDH was detected at 450 nm by microplate reader.…”
Section: Evaluation Of Cell Viabilitymentioning
confidence: 99%